The impact of sub‐national institutions: Recentralization and regional growth in the Russian Federation (2001–2008)1. Issue 3 (24th March 2016) - Leonard, Carol S.; Nazarov, Zafar; Vakulenko, Elena S.
Abstract: This paper assesses the effect of sub‐national institutions on the economic performance of Russia's regions (oblasts, republics, krais and okrugs) from 2001 to 2008, a period of rapid economic advancement and recentralization. Approximating sub‐national institutions with the RA Expert index of investment risk, we find that a reduction in investment risk by one standard deviation increases output by 1.4 percent in the short run and 11.9 percent in the long run, suggesting a substantial regional performance gap in government practices, despite intensive political recentralization. Assuming that the main components of effective governance are running satisfactory public health programmes aimed at decreasing overall mortality among the working‐age population, creating fair labour market conditions and improving the regional institutional climate to encourage investment in fixed assets, we argue that sub‐national institutions remain important for growth in post‐Soviet Russia after 2000. This paper contributes to the literature on institutional persistence.